The Resistance of the Multitude in the Age of Empire - Bilginer, Dr. Onur (International Journal of Psychosocial Rehabilitation, 2020)
In Empire, Hardt and Negri (2000) argue,national and supranational entities that coexist within the new global order operate under “a single logic of rule,” which is composed of “a new inscription of authority and a new design of the production of norms and legal instruments of coercion that guarantee contracts and resolve conflicts” (pp. xii, 9). As opposed to David Harvey’s New Imperialism, which depicts “a US-style hegemony over world affairs” established by “powerful financial centers and governmental institutions,” Hardt and Negri’s Empire neither sees this logic of rule as imperialist nor defines the U.S. as a hegemonic power (Allen, 2004, pp. 22-3). Rather, they associate imperialism with fixed territories and nation-states (i.e., Great Britain in the nineteenth century and the U.S. in the twentieth century) and then specify four main characteristics of Empire.